Pengaruh Kajian Hukum Implementasi Hybrid Contract (Akad Campuran) dalam Pembiayaan Infrastruktur Syariah: Sinkronisasi Fatwa dengan Peraturan Perundang-undangan: Pengaruh Kajian Hukum Implementasi Hybrid Contract (Akad Campuran) dalam Pembiayaan Infrastruktur Syariah: Sinkronisasi Fatwa dengan Peraturan Perundang-undangan - EDI SIREGAR (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2025)
Abstract Infrastructure development is a fundamental prerequisite for the resilience and economic growth of Indonesia. The Sharia Finance Sector holds a strategic role as an alternative funding source, particularly through the mobilization of public and private funds via Sukuk instruments. The nature of infrastructure financing—which is multibillion in scale, long-term, and structured with layered risks—necessitates the use of complex contract structures, known as the Hybrid Contract (Akad Murakkabah or Multi Akad). Substantively, the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) has provided fiqh legitimacy to mixed contracts, aligning with the principle of Maqashid Syari'ah and the flexibility of contemporary Muamalah fiqh. This research has a dual objective: first, to analyze the depth of the DSN-MUI Fatwa's juridical framework in regulating Hybrid Contracts; and second, to critically identify areas of regulatory disharmony between the Fatwa and the Financial Services Authority Regulations (POJK) in the context of infrastructure financing. Using the normative legal research method with statutory and conceptual approaches, the analysis shows that although the Hybrid Contract is valid under Sharia and has been implemented in Sukuk schemes, its legal certainty is hampered by the rigidity and limitations of product definition within positive regulation. This disharmony creates a legal gap that potentially triggers regulatory arbitrage and stifles innovation. The research recommends improving POJK to explicitly accommodate the typology of mixed contracts and optimizing the OJK's Regulatory Sandbox for complex project financing products to achieve legal certainty and stability within the national Sharia financial system.